2008
DOI: 10.1093/intimm/dxn004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of antibody responses to streptococcal and tissue antigens in patients with acute rheumatic fever

Abstract: Acute rheumatic fever (ARF) is an autoimmune disease occurring in individuals following untreated group A streptococcal infection believed to be triggered by antibodies to bacterial components that cross-react with human tissues. We developed a multiplexed immunoassay for the simultaneous quantitation of antibodies to nine streptococcal-related antigens including streptolysin O (SLO), DNase B, collagen I and IV, fibronectin, myosin, group A carbohydrate, M6 protein and streptococcal C5a peptidase. Utilizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 45 publications
2
29
0
2
Order By: Relevance
“…Although progress has been made in our understanding of disease pathogenesis, there is still much to be elucidated about the disease process. Auto-antibodies, which develop during streptococcal infection and rheumatic fever, are being investigated for their potential role [4,5,14], while it is evident that T lymphocytes play a key role in the pathogenesis of rheumatic carditis.…”
Section: Discussionmentioning
confidence: 99%
“…Although progress has been made in our understanding of disease pathogenesis, there is still much to be elucidated about the disease process. Auto-antibodies, which develop during streptococcal infection and rheumatic fever, are being investigated for their potential role [4,5,14], while it is evident that T lymphocytes play a key role in the pathogenesis of rheumatic carditis.…”
Section: Discussionmentioning
confidence: 99%
“…36 Evidences suggest that streptococcal specific antibodies and T cells may contribute to this pathology. [37][38][39][40] In the case of RHD it has been suggested that antibodies to the streptococcal sugars damage the endothelial surface of the heart valves enabling the ingress of streptococcal-specific immune cells, including CD4 and CD8 T cells [41][42][43] which are activated by cross-reactive cardiac antigens leading to inflammation and scarring. 40,44 T cells taken from the excised heart valves of acute RF patients have been analyzed for specificity and some have been shown to respond to epitopes from the M protein, 45,46 raising potential concerns that vaccines containing those epitopes may induce pathology.…”
Section: Vaccine Safetymentioning
confidence: 99%
“…Its variable N-terminal as well as its conserved carboxy-terminal region has been studied as a possible vaccine candidate (2,4,12). However, the existence of more than 100 M protein serotypes of S. pyogenes and the link between M protein-induced humoral and cellular immune responses and autoimmune poststreptococcal sequelae hinder M protein-based vaccine development (13,18,42). Several other group A streptococcal surface proteins were also shown to induce protective immune responses in animals and are therefore considered vaccine candidates; among them are the extracellular pyrogenic exotoxins, streptococcal superantigens, C5a peptidase, and the streptococcal fibronectin-binding protein SfbI (5,10,25,36,56).…”
mentioning
confidence: 99%
“…on May 10, 2018 by guest http://iai.asm.org/ to induce both humoral and cellular immunological cross-reactivity, especially with heart and joint tissues, is the M protein (11,13,18,42). Besides this link of autoimmunity to poststreptococcal sequelae, the existence of more than 100 different M types hinders M protein-based vaccine development.…”
mentioning
confidence: 99%